Pendampingan Terhadap Family Caregiver Lansia Pasca Stroke: Studi Kasus - Dinasti Pudang Binoriang; Fajar Bintara Putra (Jurnal Riset Daerah, 2024)
Post-stroke elderly need help from caregivers in carrying out daily activities. Meeting needs that continue even sometimes the elderly after a stroke need total assistance. This is what makes the Caregiver burdened. Assistance to caregivers and the elderly is needed to provide support and knowledge for caregivers in caring for the elderly. Care that has long been vulnerable to caregivers experiencing tension in providing care. Providing assistance to family caregivers so that they can care for the elderly after stroke. This writing uses the case report method which is carried out for 3 days consisting of 3 sessions of providing education related to stroke and its treatment, then treating stroke patients to accommodate vehicles and elderly treatment to health facilities. The results of this study showed that there was no change in elderly care during the 3x meeting. Caregivers still cannot bring elderly care to the elderly after stroke which consists of doing treatment, caring for the elderly and bringing the elderly to health facilities. Assistance to caregivers and the elderly who experience tension problems in the role of providing care is very important. Mentoring will be successful if it is carried out continuously with a longer period of time